Preconditioning with L-alanyl-glutamine upon cerebral edema and hypocampus red neurons counting in rats subjected to brain ischemia /reperfusion injury - Vasconcelos,Paulo Roberto Cavalcante de (2015)
PURPOSE:To evaluate the effects of the dipeptide L-alanyl-glutamine (L-Ala-Gln) as a preconditioning agent to potentially promote reduction in the intensity of lesion or induction of resilience in rats subjected to global cerebral ischemia/reperfusion (I/R) injury.METHODS:Thirty-six male Wistar rats weighing 280-300g were randomly assigned to six groups (n=6). Groups Sham 1h and 24h were treated with saline and spared of further interventions. The remaining groups were submitted to clamping of the common carotid arteries for 30 minutes (ischemia) and treated with saline (SS) or L-Ala-Gln. Brain reperfusion was allowed for 1or 24 h. L-Ala-Gln was administered intravenously (0.75g/kg) 30 minutes before sham procedure or induction of global brain I/R injury. Brain edema and red neuron counting were determined. Results were expressed as Mean±SD for normal results and Median±Percentile for non parametric data. Significance was established at p<0.05.RESULTS:Global I/R injury promoted an increase in brain edema at 24 h after reperfusion, whereas preconditioning with L-Ala-Gln induced no change in edema. On the other hand, L-Ala-Gln preconditioning decreased significantly red neurons counting both at 1h and 24h post reperfusion (p<0.05).CONCLUSION:There was a significant preconditioning effect with L-Ala-Gln decreasing cell death (red neurons counting) at early (1h) and late reperfusion (24h) in the cerebral tissue.